A novel approach to symptomatic lumbar facet joint synovial cyst injection and rupture using iGuide navigational software: A case report and review - Wang, David J (Interv Neuroradiol, 2016)
Spinal synovial cysts are benign protrusions of facet joint capsules caused by degenerative spondylosis, most frequently involving the L4–5 level, and commonly lead to symptoms of back pain, radiculopathy and neurogenic claudication. Although percutaneous treatment via facet joint steroid injection with cyst rupture can provide significant symptom relief, cyst rupture is not always achievable via an indirect trans-facet approach due to limited access from severe degenerative changes. In this case, we describe a successful approach to direct cyst access using a laser-guided navigational software in a patient with severe facet joint osteophytosis. We provide a brief review of literature.